Global sensitivities of forest carbon changes to environmental conditions. (22nd September 2021) - Besnard, Simon; Santoro, Maurizio; Cartus, Oliver; Fan, Naixin; Linscheid, Nora; Nair, Richard; Weber, Ulrich; Koirala, Sujan; Carvalhais, Nuno
Abstract: The responses of forest carbon dynamics to fluctuations in environmental conditions at a global scale remain elusive. Despite the understanding that favourable environmental conditions promote forest growth, these responses have been challenging to observe across different ecosystems and climate gradients. Based on a global annual time series of aboveground biomass (AGB) estimated from radar satellites between 1992 and 2018, we present forest carbon changes and provide insights on their sensitivities to environmental conditions across scales. Our findings indicate differences in forest carbon changes across AGB classes, with regions with carbon stocks of 50–125 MgC ha −1 depict the highest forest carbon gains and losses, while regions with 125–150 MgC ha −1  have the lowest forest carbon gains and losses in absolute terms. Net forest carbon change estimates show that the arc‐of‐deforestation and the Congo Basin were the main hotspots of forest carbon loss, while a substantial part of European forest gained carbon during the last three decades. Furthermore, we observe that changes in forest carbon stocks were systematically positively correlated with changes in forest cover fraction. At the same time, it was not necessarily the case with other environmental variables, such as air temperature and water availability at the bivariate level. We also used a model attribution method to demonstrate that atmospheric conditions were the dominant control of forest carbon changes (56% of the total study area) followed by water‐related (29% of the total study area) and vegetation (15% of the total study area) conditions. Regionally, we find evidence that carbon gains from long‐term forest growth covary with long‐term carbon sinks inferred from atmospheric inversions. Our results describe the contributions from the atmosphere, water‐related and vegetation conditions to forest carbon changes and provide new insights into the underlying mechanisms of the coupling between forest growth and the global carbon cycle. Abstract : In this study, we use a novel record of global satellite‐derived estimates of aboveground biomass (AGB) spanning almost three decades to explore the global sensitivities of forest carbon changes to environmental conditions. We report on the spatial patterns of net forest carbon changes at a global scale and how forest carbon changes are modulated by climate, water‐related (e.g. soil moisture) and vegetation conditions (e.g. LAI, NDVI and GPP) across scales. Furthermore, we investigate regionally whether carbon gains from long‐term forest growth were coupled with long‐term carbon sinks inferred from atmospheric inversion.